DESCRIPTIVE ANALYSIS OF QUALITY OF INFORMATION OF DRUGS ON ANDROID-BASED INDIAN ONLINE PHARMACY APPLICATIONS: A PRELIMINARY ANALYSIS - PERVEEN, SHAIKH SANA; SURVE, SHWETA; RP, NERURKAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objectives of the study were as follows: 1) To analyze the completeness of drug-related information of various Indian pharmacy online android applications and its readability. 2)To analyze the ease of availability of drugs and barriers to access them on these apps. Methods: A total of five popular pharmacy android apps in India (1mg, Netmeds, MedPlus, Pharmeasy, and Medikova) were chosen to analyze the prescribing information (PI) regarding five drugs, metformin, atenolol, ranitidine, ibuprofen, and alprazolam. Display of PI in these apps was compared with standard sources, i.e., National Formulary of India, Current Index of Medical Specialties, and package inserts of respective drugs. Drug-related information under 11 categories (indication, dose, contraindications, adverse events, etc.) was analyzed in these apps as complete/ incomplete. Readability of information was assessed using Flesch Reading Ease Score (FRES). These five drugs were ordered from all the apps to know the exact process to access them. Results: Categories such as indication and dose were mentioned in most apps. While, precautions and adverse events were given for few drugs in few apps. Least score was for categories like precautions in special population. FRES was minimum in Pharmeasy (30.82) and maximum in MedPlus (70.51). Valid prescriptions were demanded by all apps while one app had the facility of providing prescription from their own consultant. Only one app provided “Ask a Pharmacist” option. Conclusion: We found lots of inconsistency in the information provided by these apps. Our results are based on only five apps and provide a framework for future studies to scrutinize online apps.